Russian Freshmen Future Profession Choice in the Conditions of Digitalization: New Challenges of Labour Markets - Grunt, Elena; Lissitsa, Sabina; Lebedkina, Ekaterina (KnE Social Sciences, 2021)
The prestige and values of higher education are traditionally high in Russia and overseas countries. For several generations, there has been a youth orientation towards higher education. Higher education and diplomas are perceived by a person primarily as a means of social mobility. Profession sets a certain “social background” for people’s life. At the same time, however, over the past few decades the assessment of the prestige associated with certain professions and specialties has dramatically changed and the labor market has changed, too. The the desire for higher education among young people continues to grow in Russia. Today’s students, future specialists, face new challenges of the labor market: firstly, availability of desired and demanded professions acquisition on the labor market; secondly, disappearance of old and the emergence of new professions; thirdly, digitalization of the labor market; fourthly, the formation of specialist competencies that are in demand both on the local and global labor markets. The major research objectives were to study the issues of students’ profession choice and their opinion on the demanded / non-demanded professions on modern labor market. The research methodology combines both quantitative and qualitative approaches. The primary data was collected using questionnaires and indepth-interviews. 250 freshmen of the Ural Federal University and 250 freshmen of Saint-Petersburg State University were questioned on the basis of quota sampling. In depth-interviews (15) were organized for the educators engaged in the system of higher education. The study has revealed the issue of inequality in access to higher education as well as of inequality in access to getting prestigious and demanded professions on labor market.The majority of the respondents look for occupation suited to abilities and to their own interests. For young people the main thing is that the profession should not only make profit, but also a career progress and give new professional knowledge. The research has fixed that the majority of the students believe that they have made the right choice of specialty and they are well aware of how their future professional activity will be. About 30.0% of young people do not often choose those professions that they would like to be trained at the university, but those that are possible due to their “accessibility”. The students’ professional choice does not correspond to their ideas about their future profession and their psychological characteristics. Keywords: Higher education, students, freshmen, Russia, labor market, future profession choice, digitalization